Disparities in Physical Health Conditions Among Lesbian and Bisexual Women: A Systematic Review of Population-Based Studies. Issue 1 (2nd January 2017) - Simoni, Jane M.; Smith, Laramie; Oost, Kathryn M.; Lehavot, Keren; Fredriksen-Goldsen, Karen
ABSTRACT: We conducted a systematic review to assess evidence for disparities for lesbian and bisexual women (i.e., sexual minority women [SMW]) in comparison with heterosexual women across a range of nine physical health conditions. Among the k  = 11 studies meeting eligibility criteria, almost every comparison (i.e., heterosexual vs. (a) lesbian, (b) bisexual, or (c) both lesbian and bisexual women) was in a direction indicating SMW disparities. Despite limited power due to small samples of SMW, we found evidence of disparities as indicated by a statistically significant adjusted odds ratios for asthma (5 of 7 comparisons), obesity (8 of 12), arthritis (2 of 3), global ratings of physical health (4 of 7), and cardiovascular disease (1 of 1). Evidence was lacking for cancer (1 of 4), diabetes and hypertension (both 1 of 5), and high cholesterol (0 of 3). Future work should confirm findings in more diverse, larger samples and should examine potential explanatory factors.